2018
DOI: 10.1177/0020731418809857
|View full text |Cite
|
Sign up to set email alerts
|

The Uneven Foci of Work Disability Research Across Cause-based and Comprehensive Social Security Systems

Abstract: This scoping review identified what kinds of work disability policy issues are critiqued in articles published in countries with cause-based versus comprehensive welfare systems. Drawing on a review of work disability policy research, we identified 74 English-language, peer-reviewed articles that focused on program adequacy and design. Articles on cause-based systems dwelled on system fairness and policies of proof of entitlement, while those on comprehensive systems focused more on system design complexities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…This study took place in four municipalities in the Capital Region of Denmark, a country with a comprehensive system providing social security 10 and healthcare free of charge. 11 Compensation for lost work capacity, called sick leave benefit, is governed by municipal jobcentres and is reimbursed to the employer or directly to the person on sick leave if the citizen is unemployed.…”
Section: Study Setting and Contextmentioning
confidence: 99%
“…This study took place in four municipalities in the Capital Region of Denmark, a country with a comprehensive system providing social security 10 and healthcare free of charge. 11 Compensation for lost work capacity, called sick leave benefit, is governed by municipal jobcentres and is reimbursed to the employer or directly to the person on sick leave if the citizen is unemployed.…”
Section: Study Setting and Contextmentioning
confidence: 99%
“…Uneven foci of work disability policy research across cause-based and comprehensive social security systems were identified in a recent scoping review by MacEachen et al (2018). Articles on cause-based systems dwelled on system fairness and policies of proof of entitlement, while those on comprehensive systems focused more on system design complexities relating to worker inclusion and scope of medical certificates.…”
Section: Overarching Resources: Work and Non-work Related Legislation And Social Welfare Policymentioning
confidence: 99%
“…Overall, a clear difference in the nature of problems examined in the different systems was observed. For research to better inform policy making, the authors call for cross-pollination of research topics across the systems and more international comparison studies that are attuned to these policy differences (MacEachen et al 2018).…”
Section: Overarching Resources: Work and Non-work Related Legislation And Social Welfare Policymentioning
confidence: 99%
“…For research to better inform policy making, the authors call for cross-pollination of research topics across the systems and more international comparison studies that are attuned to these policy differences (MacEachen et al 2018).…”
Section: Overarching Resources: Work and Non-work Related Legislation...mentioning
confidence: 99%